Religion in times of crisis - Ganiel, Gladys. (Religion and the Social Order, 2014)
Religion is alive and well all over the world, especially in times of personal, political, and social crisis. Even in Europe, long regarded the most "secular" continent, religion has taken centre stage in how people respond to the crises associated with modernity, or how they interact with the nation-state. In this book, scholars working in and on Europe offer fresh perspectives on how religion provides answers to existential crisis, how crisis increases the salience of religious identities and cultural polarization, and how religion is contributing to changes in the modern world in Europe and beyond. Cases from Poland to Pakistan and from Ireland to Zimbabwe, among others, demonstrate the complexity and ambivalence of religion's role in the contemporary world.